Vibration Damping Optimization using Simulated Annealing Algorithm for Vehicle Powertrain System - Genc, M. O.; Kaya, N. (Engineering, Technology & Applied Science Research, 2020)
The clutch system in a vehicle’s powertrain system controls torque transmission and has vibration damping properties. A vehicle’s clutch system is subjected to high dynamic loads and vibrations, under operational conditions, that need further system analysis. The torque generated from the vehicle’s engine creates vibrations at different levels of frequencies. For this purpose, vibration damping systems have to be designed to make the vehicle work more efficiently. In this study, the 1-D modeling of powertrain system, including metallic clutch damper springs, was subjected to vibration optimization with the Simulated Annealing (SA) algorithm. This novel methodology accelerates the powertrain system vibration optimization and provides assumptions eliminating cost and time in real vehicle testing.